A Stability Indicating RP-HPLC Method for the Estimation of Gemcitabine HCl in Injectable Dosage forms - Shaik Mastanamma; G. Ramkumar; D. Anantha Kumar; J. V. L. N. Seshagiri Rao (E-Journal of Chemistry)
A stability indicating RP HPLC method has been developed for the determination of gemcitabine hydrochloride. Chromatography was carried out on an ODS C18 column (250×4.6 mm; 5μ) using a mixture of methanol and phosphate buffer (40: 60 v/v ) as the mobile phase at a flow rate of 1.0 mL/min. The detection of the drug was monitored at 270 nm. The retention time of the drug was found to be 2.31 min. The method produced linear responses in the concentration range of 10 to 60 μg/mL of gemcitabine HCl. The method was found to be reproducible for analysis of the drug in injectable dosage forms. The stability of the drug was assessed by forced degradation studies.